2006
DOI: 10.1897/05-030r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐additive inhibition of chinook salmon acetylcholinesterase activity by mixtures of organophosphate and carbamate insecticides

Abstract: Organophosphate and carbamate insecticides are widely detected in surface waters of the western United States. These chemicals interfere with acetylcholine-mediated synaptic transmission in the nervous systems of fish and other aquatic animals via the inhibition of AChE (acetylcholinesterase) enzyme activity. Anticholinesterase insecticides commonly co-occur in the environment. This raises the possibility of antagonistic, additive, or synergistic neurotoxicity in exposed fish, including threatened and endanger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 41 publications
1
31
1
Order By: Relevance
“…Inhibition of the enzyme acetylcholinesterase (AChE) activity results in the buildup of acetylcholine (ACh) at cholinergic nerve endings causing continual nerve stimulation (Scholz et al 2006). Inhibition of AChE activity occurs in the central nervous system (CNS) and in the plasma and muscle of fish (Perkins and Schlenk 2000).…”
Section: Toxicity Of Carbamates and Organophosphatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the enzyme acetylcholinesterase (AChE) activity results in the buildup of acetylcholine (ACh) at cholinergic nerve endings causing continual nerve stimulation (Scholz et al 2006). Inhibition of AChE activity occurs in the central nervous system (CNS) and in the plasma and muscle of fish (Perkins and Schlenk 2000).…”
Section: Toxicity Of Carbamates and Organophosphatesmentioning
confidence: 99%
“…Salmon populations are faced with many environmental stressors including intense fishing pressure, parasites and disease, climatic variability and change, land development, hatchery production, hydropower operations, stormwater runoff, and others (NMFS 2010;Spromberg and Scholz 2011). The potential for toxic effects to Pacific salmon from exposure to pesticide mixtures has been the subject of serious debate in recent years (e.g., Scholz et al 2006;Laetz et al 2009;NMFS 2010;Lisker et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The widespread contamination of surface waters and sediments, in particular, appears to be a limiting factor for the recovery of some of these threatened wild salmon stocks. Water quality monitoring conducted by the United States Geological Survey (Gilliom et al, 2006) have indicated that many Pacific Northwest surface waters contain pesticide residues, oftentimes in river beds used by salmon for spawning and during the early life stages of the fry (Scholz et al, 2006). Pollutants in water may affect the physiology of fish olfaction, disrupting biologically-relevant signals essential in their behavior that ultimately affect species survival (Klaprat et al, 1992;Moore & Waring, 1996;Scott et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Such effects would be expected to be dose dependent. Scholz et al (2006) The present document has been produced and adopted by the bodies identified above as author(s). This task has been carried out exclusively by the author(s) in the context of a contract between the European Food Safety Authority and the author(s), awarded following a tender procedure.…”
Section: Figurementioning
confidence: 99%